2022
DOI: 10.3389/fphar.2022.861183
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible Nitric Oxide Synthase Dimerization Inhibitor Prevents the Progression of Osteoarthritis

Abstract: Objective: Osteoarthritis (OA) is a degenerative joint disease. Excessive nitric oxide (NO) mediates the chondrocyte inflammatory response, apoptosis, and extracellular matrix (ECM) degradation during the occurrence and development of OA. NO in chondrocytes is mainly produced by inducible nitric oxide synthase (iNOS). The aim of this study was to design and synthesize an iNOS dimerization inhibitor and evaluate its effects on chondrocyte inflammation and articular cartilage injury in OA via in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Then, the NO in turn activates NF‐κB in a p38MAPK‐dependent manner, forming a positive feedback pathway that promotes apoptosis. Some research focus on reducing the production of ROS and NO, and so on, so as to inhibit IL‐1β‐induced apoptosis and inflammation progression 51–54 . However, it has been suggested that the effect of ROS on NF‐κB may be related to the duration of oxidative stress, so the sustained oxidative stress may instead inhibit NF‐κB activity 55 …”
Section: Introductionmentioning
confidence: 99%
“…Then, the NO in turn activates NF‐κB in a p38MAPK‐dependent manner, forming a positive feedback pathway that promotes apoptosis. Some research focus on reducing the production of ROS and NO, and so on, so as to inhibit IL‐1β‐induced apoptosis and inflammation progression 51–54 . However, it has been suggested that the effect of ROS on NF‐κB may be related to the duration of oxidative stress, so the sustained oxidative stress may instead inhibit NF‐κB activity 55 …”
Section: Introductionmentioning
confidence: 99%
“…COX-2 and mPGES-1 are both responsible for prostaglandin E 2 (PGE 2 ) synthesis, while iNOS produces nitric oxide (NO). PGE2 and NO also take part in ECM catabolism, leading to cartilage degradation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%